Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x\(^2\)+8x +15
=( x\(^2\)+3x) + ( 5x +15)
= x(x+3)+ 5 (x+3)
=(x+3) (x+5)
b)x\(^2\)-4x-12
=( x\(^2\)- 6x) +( 2x -12)
=x(x-6) + 2 (x-6)
=(x - 6) (x+2)
c)9x\(^2\)-6x-24
=(9x\(^2\)-18x)+ (12x-24)
=9x(x-2) + 12 (x -2 )
=(x-2) (9x+12)
a) \(x^2+8x+15\)
\(=x^2+8x+16-1\)
\(=\left(x^2+8x+16\right)-1\)
\(=\left(x+4\right)^2-1\)
\(=\left(x+4-1\right)\left(x+4+1\right)\)
\(=\left(x+3\right)\left(x+5\right)\)
b) \(x^2-4x-12\)
\(=x^2-4x+4-16\)
\(=\left(x^2-4x+4\right)-4^2\)
\(=\left(x-2\right)^2-4^2\)
\(=\left(x-2-4\right)\left(x-2+4\right)\)
\(=\left(x-6\right)\left(x+2\right)\)
c) \(9x^2-6x-24\)
\(=9x^2-6x+1-25\)
\(=\left(9x^2-6x+1\right)-5^2\)
\(=\left(3x-1\right)^2-5^2\)
\(=\left(3x-1-5\right)\left(3x-1+5\right)\)
\(=\left(3x-6\right)\left(3x+4\right)\)
Ta có
\(x^3-6x^2+x^2y+9x-3y\\ =\left(x^3-6x^2+9x\right)+\left(x^2y-3y\right)\\ =x\left(x^2-3\right)^2+y\left(x^2-3\right)\)
=(x^2-3)(x+y)
d) x3-4x2-9x+36
=x2(x-4)-9(x-4)
=(x-4)(x2-9)
=(x-4)(x+3)(x-3)
e)(x+1)3+(2x-1)3
=x3+3x2+3x+1+8x3-12x2+6x-1
=9x3-9x2+9x
=9x(x2-x+1)
g)x3+3x2-4x-12
=x2(x+3)-4(x+3)
=(x+3)(x2-4)
=(x+3)(x+2)(x-2)
h) x3-4x2+4x-1
=x3-1-4x2+4x
=(x-1)(x2+x+1)-4x(x-1)
=(x-1)(x2+x+1-4x)
=(x-1)(x2-3x+1)
\(\left(x-2\right)^3-1=\left(x-2\right)\left[\left(x-3\right)^2+x-2\right]=\left(x-2\right)\left(x^2+5x+7\right)\)
\(\left(x+3y\right)^2-9y^2=x\left(x+6y\right)\)
\(\left(x+3\right)^2-\left(x-1\right)^2=4\left(2x+4\right)=8\left(x+2\right)\)
a) \(\left(x-2\right)^3-1=\left(x-2\right)^3-1^3=\left(x-2-1\right)\left[\left(x-2\right)^2+\left(x-2\right)\cdot1+1^2\right]\)\(=\left(x-3\right)\left(x^2-4x+4+x-2+1\right)\)
\(=\left(x-3\right)\left(x^2-3x+3\right)\)
b) \(\left(x+3y\right)^2-9y^2\)
\(=\left(x+3y\right)^2-\left(3y\right)^2\)
\(=\left(x+3y+3y\right)\left(x+3y-3y\right)\)
\(=x\left(x+6y\right)\)
c) \(\left(x+3\right)^2-\left(x-1\right)^2\)
\(=\left(x+3-x+1\right)\left(x+3+x-1\right)\)
\(=4\left(2x+2\right)\)
\(=8\left(x+1\right)\)
\(x^8+3x^4+4\)
\(=\left(x^8-x^6+2x^4\right)+\left(x^6-x^4+2x^2\right)+\left(2x^4-2x^2+4\right)\)
\(=x^4\left(x^4-x^2+2\right)+x^2\left(x^4-x^2+2\right)+2\left(x^4-x^2+2\right)\)
\(=\left(x^4+x^2+2\right)\left(x^4-x^2+2\right)\)
\(4x^4+4x^3+5x^2+2x+1\)
\(=\left(4x^4+2x^3+2x^2\right)+\left(2x^3+x^2+x\right)+\left(2x^2+x+1\right)\)
\(=2x^2\left(2x^2+x+1\right)+x\left(2x^2+x+1\right)+\left(2x^2+x+1\right)\)
\(=\left(2x^2+x+1\right)^2\)
\(a,4x^2-12xy+9y^2=\left(2x-3y\right)^2\)
\(b,x^2-9x+20=x^2-4x-5x+20\)
\(=x\left(x-4\right)-5\left(x-4\right)\)
\(=\left(x-4\right)\left(x-5\right)\)
\(c,x^2+7x+12=x^2+3x+4x+12\)
\(=x\left(x+3\right)+4\left(x+3\right)\)
\(=\left(x+3\right)\left(x+4\right)\)
1)\(4x^2+32+64\)
\(\Leftrightarrow\left(2x\right)^2+32x+8^2\)
\(\Leftrightarrow\left(2x+8\right)^2\)
2) \(24-3y^2x=3\left(8-y^2x\right)\)
3) \(\left(x-12\right)^2-9\)
\(\Leftrightarrow\left(x-12-9\right)\left(x-12+9\right)\)
\(\Leftrightarrow\left(x-21\right)\left(x-3\right)\)
1.4x2+32x+64
=4(x2+8x+16)
=4(x+4)^2